Ophiopogonin D mitigates doxorubicin-induced cardiomyocyte ferroptosis through the β-catenin/GPX4 pathway - Lei, Yanping; Xu, Lewu; Liu, Rui; Zhao, Yue (Frontiers in Pharmacology, 2025)
BackgroundThe chemotherapeutic agent doxorubicin has the side effect of inducing injury to cardiomyocytes. Ferroptosis plays an essential role in the onset and progression of cardiac injury. Ophiopogonin D is considered the active component of the Chinese herbal medicine Mai Dong, which is commonly used for the treatment of cardiovascular diseases. This study investigates the impact of ophiopogonin D on doxorubicin-induced cardiomyocyte ferroptosis by focusing on the β-catenin/GPX4 signaling pathway.MethodsMice were injected intraperitoneally with doxorubicin (10 mg/kg) to create a model of cardiotoxicity. Cardiomyocytes exposed to doxorubicin (1 μM) were treated with ophiopogonin D (5 μM). Western blotting was used to detect β-catenin, FTH1, and GPX4. Malondialdehyde (MDA), glutathione (GSH), and Fe2+ levels were measured using biochemical assays. In addition, GPX4 expression was detected by immunohistochemistry and immunofluorescence staining. Mitochondrial injury was examined by transmission electron microscopy. Chromatin immunoprecipitation (ChIP) combined with dual-luciferase reporter gene assay was used to analyze the interaction between β-catenin and the promoter of the GPX4 gene.ResultsDoxorubicin inhibited β-catenin activity and GPX4 expression, promoting cardiomyocyte ferroptosis in vitro and in vivo. Ophiopogonin D increased β-catenin expression and promoted GPX4 expression, thereby inhibiting doxorubicin-induced ferroptosis in cardiomyocytes. Moreover, β-catenin overexpression enhanced GPX4 expression and alleviated homocysteine-induced ferroptosis in cardiomyocytes. Furthermore, results from the ChIP and dual-luciferase reporter assays indicated that GPX4 acted as a target gene of β-catenin.ConclusionOphiopogonin D inhibits cardiomyocyte ferroptosis induced by doxorubicin by restoring the β-catenin/GPX4 signaling pathway.